Characterization of Protease Crude Extract from Indigenous Lactic Acid Bacteria and the Protein Degradation Capacity in Local Tuber and Cereal Paste Flour - Tatik Khusniati; Nanda Sabbaha Nur Kasfillah; Vilya Syafriana; Resti Sofia Zahara; Padmono Citroreksoko; Sulistiani Sulistiani; Trisanti Anindyawati (Research Center for Chemistry - LIPI, 2019)
Protease hidrolyzed protein in flour in order to more digest by human ulcer. Lactobacillus plantarum B110 and Lactobacillus satsumensis are indigenous lactic acid bacteria that produce protease. The objective of this research is to characterization of protease crude extract from indigenous lactic acid bacteria and the protein degradation capacity in local tuber and cereal paste flour. Tuber and cereal flour used were purple sweet potato (Dioscorea alata), cassava (Manihot esculenta), rice (Oryza sativa), corn (Zea mays) and wheat (Triticum) as comparison. Proteaseactivity was tested by Horikoshi method (1971) and protein degradation was by formol titration. Research results showed that optimum activities and stabilities of Lactobacillus plantarum B110 were at pH: 7.5, 45oC and pH:5.0-8.0, 35-50oC, while that L. satsumensis EN 38-32 were at pH: 7.0, 40oC and pH:6.0-8.0, 20-45oC. Increases in protein degradation capacity of the paste flour additional proteases crude extract from L. plantarum B110 were 0.0838% (purple sweat potato), 1.3299% (cassava), 0.5834% (corn), 0.7499% (rice) and 1.5551% (wheat as comparison); while that L. satsumensis EN 38-32 were 0.20% (purple sweet potato), 0.32% (cassava), 0.87% (corn), 1.17% (rice). Based on increases in protein degradation capacity, protease crude extract from L. plantarum B110Â and L. satsumensis EN 38- 32 were sequently better to hidrolyze protein of cassava and rice paste flour than thatother tuber and cereal.